2011
DOI: 10.1002/dc.21427
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathologic features of secondary peripheral ameloblastic carcinoma: A case report

Abstract: Peripheral ameloblastic carcinoma is an extremely rare odontogenic tumor derived from the remnants of dental lamina and/or mucosal epithelium of the oral mucosa. We present a case of secondary peripheral ameloblastic carcinoma of the mandibular gingiva. The patient was a 71-year-old man with gingival swelling and persistent bleeding. Exfoliative cytology revealed cohesive clusters composed of basaloid cells with nuclear atypia and various forms of keratinized cells of dysplastic squamous appearance. Some cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…There are only two cases of ameloblastic carcinoma diagnosed by FNAB in the literature (15,19), which have the same cytological features of the present case. Sharma et al (20) reported a case of malignant ameloblastoma that had malignant features, as atypical mitosis and vascular invasion, only at histology, showing that the cytological diagnosis of malignancy can be difficult.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…There are only two cases of ameloblastic carcinoma diagnosed by FNAB in the literature (15,19), which have the same cytological features of the present case. Sharma et al (20) reported a case of malignant ameloblastoma that had malignant features, as atypical mitosis and vascular invasion, only at histology, showing that the cytological diagnosis of malignancy can be difficult.…”
Section: Discussionmentioning
confidence: 82%
“…The patient of this case presented a painless swelling in the right mandible angle, the most common sign and site of ameloblastic carcinoma. Her age was different from most cases described, but there are cases of ameloblastic carcinoma in patients over 70 years of age (15).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[5] Ameloblastic carcinomas arising from peripheral ameloblastomas are exceedingly rare, with only approximately eleven cases of peripheral ameloblastic carcinoma having been reported to date, including one case of an initially benign appearing peripheral ameloblastoma recurring as ameloblastic carcinoma. [4,[6][7][8][9][10] Although there have been no prior studies demonstrating the relationship between non-Hodgkin lymphoma or radiation and the development of peripheral ameloblastoma, a retrospective study evaluating 322 non-Hodgkin lymphoma cases found a significantly increased risk for head and neck cancers among patients receiving radiation therapy for early-stage non-Hodgkin lymphoma. [11] Peripheral ameloblastomas typically manifest as slowgrowing, firm, painless masses, which can be sessile or pedunculated with a smooth, granular, or warty surface.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, recurrence is attributed to incomplete removal. Long-term follow-up is necessary, as cases of benign PA have been reported to recur and present as ameloblastic carcinoma 17 18…”
Section: Discussionmentioning
confidence: 99%